2015
DOI: 10.1093/jxb/erv145
|View full text |Cite
|
Sign up to set email alerts
|

First insights into the genotype–phenotype map of phenotypic stability in rye

Abstract: HighlightYield stability in rye is controlled by many QTLs with small effects. This is in contrast to phenotypic stability of several quality traits, which are influenced by some large-effect QTLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 53 publications
3
18
0
Order By: Relevance
“…The first high-throughput genotyping technology was established for rye in 2009 with the development of a 1520-clone DArT genotyping panel (Bolibok-Bragoszewska et al, 2009). Since then, it was successfully applied for high density genetic map construction, both in rye and triticale (Bolibok-Bragoszewska et al, 2009; Milczarski et al, 2011; Tyrka et al, 2011, 2015), genome-wide germplasm characterization (Bolibok-Bragoszewska et al, 2014), QTL/gene mapping (Stojałowski et al, 2011; Miedaner et al, 2012; Myśków et al, 2012; Milczarski et al, 2016), and genomic selection (Wang et al, 2014, 2015; Schulthess et al, 2015). Following transcriptome sequencing a Rye5K SNP genotyping panel was developed and used for construction of high density transcript map (Haseneyer et al, 2011; Martis et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The first high-throughput genotyping technology was established for rye in 2009 with the development of a 1520-clone DArT genotyping panel (Bolibok-Bragoszewska et al, 2009). Since then, it was successfully applied for high density genetic map construction, both in rye and triticale (Bolibok-Bragoszewska et al, 2009; Milczarski et al, 2011; Tyrka et al, 2011, 2015), genome-wide germplasm characterization (Bolibok-Bragoszewska et al, 2014), QTL/gene mapping (Stojałowski et al, 2011; Miedaner et al, 2012; Myśków et al, 2012; Milczarski et al, 2016), and genomic selection (Wang et al, 2014, 2015; Schulthess et al, 2015). Following transcriptome sequencing a Rye5K SNP genotyping panel was developed and used for construction of high density transcript map (Haseneyer et al, 2011; Martis et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies concluded that genomic prediction for yield stability in rye 9 and wheat 10 could be effective. However, to fully exploit plasticity it is important to understand its genetic architecture.…”
mentioning
confidence: 99%
“…Third, the structural (or regulatory) gene model states that plastic responses are caused by the regulation of mean phenotype genes by genes that integrate environmental stimuli 14,15 . Numerous studies involving modest numbers of genotypes have found evidence for both the allelic sensitivity and structural gene models to varying degrees in various organisms and phenotypes 9,1620 .…”
mentioning
confidence: 99%
“…Hybrid rye breeding started in Germany as early as in the 1970s, and the first hybrid cultivar was released in 1984 (Geiger and Miedaner, 1999). Recently, hybrid breeding programs have been started in Russia, Poland, Belarus, and Sweden (Tomerius et al, 2008;Wang et al, 2015). In multilocal testing trials, rye hybrids yielded ~10% higher than standard population cultivars; they are also shorter, have better resistance to preharvest sprouting, and demonstrate unchanged lodging resistance (Schlegel, 2006).…”
mentioning
confidence: 99%